Disaster readiness and risk reduction management module using Kolb’s model - Mayflor Galleno Agustin; Marie Grace S. Cabansag (Institute of Advanced Engineering and Science, 2023)
Disaster risk reduction and management (DRRM) as a course in basic education aims to raise the student’s awareness of what to do before, during, and after a disaster using contextualized modules. The contextualization and validation of these modules considered legal bases and statutory standards in terms of learning competency, content, language, assessment, format, and technical specifications. The student’s performance and end users’ feedback and suggestions were used as bases for evaluating the developed modules. The descriptive method thru the instrumentation technique of research followed the process of module development from the planning phase to the evaluation following the analysis, design, development, implementation dan evaluation (ADDIE) model while the module sections used the Kolb’s model. The respondents were senior high school students in the Science curricular program of Echague National High School and Isabela State University, Isabela, Philippines. The findings showed a good agreement among experts’ ratings and ascertained compliance with the learning resources guidelines of the Department of Education, Philippines. The student’s performance on their post-test was significantly higher than their pre-test scores. The student’s interests and learning engagement were very high as shown in their performance in activities and assessments. The contextualized DRRM modules are recommended for classroom use for on-site and distance learning modalities.